Crystallization and preliminary X-ray crystallographic studies of Protac (R), a commercial protein C activator isolated from Agkistrodon contortrix contortrix venom - Murakami, M. T.; Arni, R. K. (Elsevier B.V., 2005)
The protein C pathway plays an important role in the control and regulation of the blood coagulation cascade and prevents the propagation of the clotting process on the endothelium surface. In physiological systems, protein C activation is catalyzed by thrombin, which requires thrombomodulin as a cofactor. The protein C activator from Agkistrodon contortrix contortrix acts directly on the zymogen of protein C converting it into the active form, independently of thrombomodulin. Suitable crystals of the protein C activator from Agkistrodon contortrix contortrix were obtained from a solution containing 2 M ammonium sulfate as the precipitant and these crystals diffracted to 1.95 angstrom resolution at a synchrotron beamline. The crystalline array belongs to the monoclinic space group C2 with unit cell dimensions a=80.4, b = 63.3 and c = 48.2 angstrom, alpha = gamma = 90.0 degrees and beta = 90.8 degrees. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: protein C activator; serine proteinase; Agkistrodon contortrix contortrix venom; X-ray diffraction analysis